Intrinsic Rewards and Intrinsic Motivation: An Evidence from Middle Level Employees Working in Apparel Industry - Nirojan, J.; Renusha, M. (International Conference on Contemporary Management [ICCM]-2021], 2021)
The pivotal focus of every organization is to enhance the ultimate performance of the employees. Hence, organizations are used different motivation tools in a tactical way. A person is intrinsically motivated if he/she performs an activity for no apparent reward except the activity itself. In that way organizations motivate their employees through fulfillment of their employee's expectation by the means of rewards. Employees feel happy and motivated when their superiors treat them with great appreciation, give new challenges, caring attitude, and recognition rather than those benefits are given by the monetary benefit from the organization. Indeed, motivation is primarily a basic drive to individual to work hard. In the workplace, it is especially important to motivate employees so that they meet their full potential. In fact, apparel employees should be available more time in all days due to work load. Thus this research is aimed at identifying the impact of intrinsic rewards on employees' intrinsic motivation in apparel sector. The data was collected by using survey method. Population was the middle level employees from apparel sector and 165 employees who are conveniently selected since, the collection of data seems to be difficult during pandemic. Data analyses were done by the use of Statistical Package for Social Sciences (SPSS). In it, regression analysis was done. This study evidenced that the impact of reward system on employee motivation in the apparel sector employees in Sri Lanka is existing as the intrinsic reward is one of the prime factor which enhances to work of employees in apparel sector.
Keywords: Apparel sector; Intrinsic reward; Intrinsic motivation